As margens do Piraquê-Açu : etnogênese e território : uma abordagem geográfica - Florêncio, Carlos Manuel Diogo da Luz (2010)
This work addresses the “Ethnogenesis” of Tupiniquim and Guarani populations in the municipality of Aracruz in Espírito Santo Brazil, which happened in the past fifty years. The area of land reserved under the law as Indian land, does have frontier with other areas which are currently being classified as protected areas in a variety of territorial uses an conflicting territorial disputes over land tenure, of low intensity use, with eucalyptus monoculture, for use and protection of estuaries and marchlands with economic relationship between populations of traditional Piraquê-Mirim estuaries. Such populations are concentrated on the north bank of the estuary. Starting from the indigenous and territorial issues, through the study of objective and subjective approaches a few conceptual considerations on ethnogenesis, space, living space, territory, state, globalization emerged as a result of the dynamics of the relevant research as well as from Geographical reflection that presents a scenario of anthropic activities which results from continued industrialization and industry unit and broad expansion of the port sector.